Application of a-Si:H in p-i-n Solar Cell by VHF-PECVD Method - I. Usman; A. Supu; Mursal Mursal; Sukirno, T. Winata; M. Barmawi (Institut Teknologi Bandung, 2004)
The a-Si:H p-i-n solar cells have been deposited on Corning glass coated with Transparent Conductive Oxide (TCO) by employing the VHF-PECVD method at the substrate temperature of 275 oC. The 10% SiH4 gas diluted in H2 was used as a gas source and the doping process was done by gas admixture of B2H6 and PH3 for p- and n-layer respectively. A careful mono-layer optimization such as power discharge and deposition pressure was done to obtain the best a-Si:H film quality. The deposition rate (rd), optical bandgap (Eopt), and photoconductivity (σph) of i-layer was obtained are 2.04 Å/s, 1.69 eV, and 9.23 x 10-5 S/cm, respectively. Two different solar cells were then fabricated by applying the active layer (i-layer) of 4400Å and 5500Å thickness, while the thicknesses of p- and n-layer were fixed to 150Å and 300Å respectively. The current-voltage measurement under 34 mW/cm2 light illumination shows higher value of VOC, ISC, and efficiency which are of 0.77 Volt, 15.92 mA/cm2, and 9.39%, respectively for the solar cell with thicker i-layer of 5500Å.